Peer Learning Practices of the Graduates Pursuing Master's Degree in Rural Development, Social Work, and Health Education Subjects in University Campus, Kirtipur, Kathmandu (Punyawati Journal, 2026)
The global higher education is experiencing a shift of traditional, instructor-based models of instruction towards the more interactive, learner-based pedagogies. This research paper examines the peer learning among the Master students of University Campus, Kirtipur in terms of their frequency, typologies, determinants, and correlation with academic performance. They used a cross-sectional survey design where the sample comprised of 112 respondents who were participants of the Social Work, Rural Development, and Health Education programmes, and were administered questionnaires that were analyzed using statistical tools. Findings show that peer learning has a high rating as a strategy to create social interaction (Mean = 4.37) and also to prepare and do exams but has a more variable rating on deep conceptual understanding (Mean = 3.64). The use of technology, role of learning and the notion of instructor support showed that there were differences of discipline and demography. Social Work students were found to exhibit more organized interaction based on formal platforms (68.2% using Google Classroom) and Health Education students had a preference towards less formal interaction which was more peer-centered. Chi-square tests showed that the subject stream and platform choice were statistically significant (χ 2 = 28.76, p =.001) and that the perceived grade improvement were statistically significant ( 2 = 31.17, p =.001). The research confirms the socio-affective benefits of peer learning and highlights the need to implement them in a more systematic way to better cognitive outcomes and guide evidence-based educational policy.